Project To Strengthen the Profile of Pancasila Youth at Madrasah Aliyah Al Furqon Bugul Lor Panggungrejo Pasuruan - Mashuda (Gayaku Publisher, 2024)
The project to strengthen the profile of Pancasila youth or P5 is an interdisciplinary learning that aims to observe and think about solutions to problems in the surrounding environment. Madrasah Aliyah Al Furqon Bugul Lor is also one of those who implement it, researchers who happen to practice teaching there are involved in every P5 project activity with the theme of entrepreneurship by utilizing surrounding ingredients which are local wisdom such as making a refreshing and healthy drink